2010
DOI: 10.1111/j.1526-4637.2010.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Transforaminal Injection of Steroids for the Treatment of Lumbar Radicular Pain

Abstract: Transforaminal injection of steroids is effective only in a proportion of patients. Its superiority over other injections is obscured when group data are compared but emerges when categorical outcomes are calculated. Over time, the proportion of patients with maintained responses diminishes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
294
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(303 citation statements)
references
References 50 publications
3
294
2
4
Order By: Relevance
“…Where reported, injected nerve root levels were L4-S1 in two studies 43,46 and L2-S1 in one study. 42 The local anaesthetic injected varied between the studies, anaesthetic volume ranged from 1 ml to 6 ml, and anaesthetic concentration, reported in five studies, 25,42,[44][45][46] ranged from 0.25% to 1%. Three studies 25,44,46 used an injectable steroid as well as the anaesthetic.…”
Section: Summary Of Test Accuracy Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Where reported, injected nerve root levels were L4-S1 in two studies 43,46 and L2-S1 in one study. 42 The local anaesthetic injected varied between the studies, anaesthetic volume ranged from 1 ml to 6 ml, and anaesthetic concentration, reported in five studies, 25,42,[44][45][46] ranged from 0.25% to 1%. Three studies 25,44,46 used an injectable steroid as well as the anaesthetic.…”
Section: Summary Of Test Accuracy Resultsmentioning
confidence: 99%
“…Table 6). One study was a diagnostic cohort study, 28 one was a RCT 42 and five studies were case series. 25,[43][44][45][46] Publication dates ranged from 1973 to 2010.…”
Section: Summary Of Test Accuracy Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they have limitations when used alone. A randomized study reported that only 54% of patients with lumbar HNP responded to TFESI [30]. Another study reported that 43-75% of patients did not have long-term effects after TFESI for acute low back pain [3].…”
Section: Discussionmentioning
confidence: 99%